Application of Trichoderma Harzianum as Soil Treatment and Additional Treatment for Control of Potato Diseases - Sutarman (Faculty of Agriculture, Merdeka University Surabaya, 2019)
This study aims to determine the effect of biofungicide application with Trichoderma harzianum as its active ingredient in the form of soil treatment and additional treatment which includes seed treatment, canopy surface spraying, and combined seed treatment and canopy spraying with Trichoderma biofungicides and active chemical fungicides mancozeb and cymoxanil, against leaf blight disease index caused by Phytopthora infestans, stover dry weight, healthy potato tuber weight, rotten tuber weight, and relative quality index of potato plant bulbs. Experiments were carried out in the Split-plot Design using a completely randomized design (CRD). The main plot is soil tretament biofungicide Trichoderma, including without soil tretament and with soil treatment. As plot saplings is an additional treatement of Trichoderma biofungicide, consisting of: chemical fungicide, seed treatement, canopy spraying, and spraying of canopy and seed treament. Each treatment was repeated 4 times, to obtain 32 experimental units. The variables observed were leaf blight disease index at the end of the vegetative phase, stover dry weight, healthy tuber weight, rotten tuber weight, and relative index of tuber quality. The results showed that the interaction of soil treatment and additional treatment of Trichoderma biofungicide had a very significant effect on the disease index of potato leaf blight, rotten tuber weight per plant, and relative index of quality of potato tubers, but did not significantly affect the dry weight of stover and tubers of healthy potatoes per plant. The combination of soil treatment and additional treatment resulted in a decrease in the disease index of 45.37 to 53.96%, a decrease in rotten tubers from 42.39 to 91.50%, and an increase in the percentage of relative index of tuber quality from 7.8 to 65.5% compared to only using fungicides made from mancozeb and cymoxanil.